2017
DOI: 10.1074/jbc.m117.797332
|View full text |Cite|
|
Sign up to set email alerts
|

The host-cell restriction factor SERINC5 restricts HIV-1 infectivity without altering the lipid composition and organization of viral particles

Abstract: The host-cell restriction factor SERINC5 potently suppresses the infectivity of HIV, type 1 (HIV-1) particles, and is counteracted by the viral pathogenesis factor Nef. However, the molecular mechanism by which SERINC5 restricts HIV-1 particle infectivity is still unclear. Because SERINC proteins have been suggested to facilitate the incorporation of serine during the biosynthesis of membrane lipids and because lipid composition of HIV particles is a major determinant of the infectious potential of the particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 72 publications
0
79
0
Order By: Relevance
“…Little is known about the function of SERINCs, despite their recent identification as HIV restriction factors 53 55 and their high degree of conservation in all branches of eukaryotes. They were originally proposed to mediate the incorporation of serine into membrane lipids 56 , but recent functional studies have shown no effect on membrane composition 57 , 58 . Our discovery that ATG9A and SERINCs are trafficked together suggests a functional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the function of SERINCs, despite their recent identification as HIV restriction factors 53 55 and their high degree of conservation in all branches of eukaryotes. They were originally proposed to mediate the incorporation of serine into membrane lipids 56 , but recent functional studies have shown no effect on membrane composition 57 , 58 . Our discovery that ATG9A and SERINCs are trafficked together suggests a functional relationship.…”
Section: Discussionmentioning
confidence: 99%
“…This activity suggested a model in which SERINCs inhibit HIV-1 infectivity by modifying the lipid content of progeny virions. However, a study argues strongly against this hypothesis by showing that SERINC5 does not alter the lipid composition of HIV-1 progeny virions or the exposure of phosphatidylserine on their surface (Trautz et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…These alterations reduce activation-induced cell death and thus prolong the survival of productively infected cells (27). Finally, Nef enhances the infectivity of HIV particles by antagonizing the restriction factors SERINC 3 and 5 via yet to be determined mechanisms (28)(29)(30)(31).…”
Section: Hiv-1 Nef Disrupts Cd4 + T Lymphocyte Polarity Extravasatiomentioning
confidence: 99%